Contribuição ao estudo químico e biológico de vitex agnus castus l. - Souza, Antônia Lúcia de (2003)
This work describe the phytochemystry study of Vitex agnus castus L. (Verbenaceae), native plant from the Mediterranean region, adapted in Brasil, where known populary as "pau-d'angola", "pimenta dos monges" and "alecrim-pimenta" [...]